Training and Detraining Effects Following a Static Stretching Program on Medial Gastrocnemius Passive Properties - Nakamura, Masatoshi; Yahata, Kaoru; Sato, Shigeru; Kiyono, Ryosuke; Yoshida, Riku; Fukaya, Taizan; Nunes, João Pedro; Konrad, Andreas (Frontiers in Physiology, 2021)
A stretching intervention program is performed to maintain and improve range of motion (ROM) in sports and rehabilitation settings. However, there is no consensus on the effects of stretching programs on muscle stiffness, likely due to short stretching durations used in each session. Therefore, a longer stretching exercise session may be required to decrease muscle stiffness in the long-term. Moreover, until now the retention effect (detraining) of such an intervention program is not clear yet. The purpose of this study was to investigate the training (5-week) and detraining effects (5-week) of a high-volume stretching intervention on ankle dorsiflexion ROM and medial gastrocnemius muscle stiffness. Fifteen males participated in this study and the plantarflexors of the dominant limb was evaluated. Static stretching intervention was performed using a stretching board for 1,800 seconds at 2 days per week for 5-week. Dorsiflexion ROM was assessed, and muscle stiffness was calculated from passive torque and muscle elongation during passive dorsiflexion test. The results showed significant changes in dorsiflexion ROM and muscle stiffness after the stretching intervention program, but the values returned to baseline after the detraining period. Our results indicate that high-volume stretching intervention (3,600 seconds per week) may be beneficial for dorsiflexion ROM and muscle stiffness, but the training effects are dismissed after a detraining period with the same duration of the intervention.